Analyzing Differences in Viral Dynamics Between Vaccinated and Unvaccinated RSV Patients - Arjan Suri; Sahaj Satani; Hana M. Dobrovolny (Epidemiologia)
Background: Respiratory syncytial virus (RSV) is a common respiratory virus that can cause serious illness in infants and the elderly. Vaccines for RSV have recently been introduced and have been shown to reduce the severity of the disease. However, there has been limited examination of how viral dynamics differ between vaccinated and unvaccinated individuals. Methods: Here, we use data from the MVA-BN-RSV Phase II vaccine study to quantify the dynamical differences between vaccinated and unvaccinated patients challenged with RSV. We use an ordinary differential equation model of within host viral dynamics to fit viral load data. Results: We find statistically significant differences in viral clearance rate and basic reproduction number. We also find that vaccinated patients experience a higher response variance than the placebo group. Conclusions: While the differences in viral clearance and basic reproduction number are promising, the high variability in response to the vaccine could leave many vaccinated patients without adequate protection.